Heat transfer in turbulent planar offset attaching jets with small initial offset distances. (April 2015) - Gao, N.; Ewing, D.; Ching, C.Y.
Abstract: Measurements of the mean heat transfer coefficient from the wall below turbulent offset wall attaching planar jets were performed for jets with Reynolds numbers ( Re j ) of 21, 800–54, 500. The jets were initially offset 0.2–1 times the initial jet height ( H j ) above the wall. The Reynolds number dependence of the maximum Nusselt number varied with offset distance from Re j 0.64 for the flows with an offset distance of 0.2 H j to Re j 0.77 for flows with initial offset distances of H j . The distance from the jet exit to the location of the maximum heat transfer coefficient also increased with Reynolds number for the jets with smaller offset distances. The maximum heat transfer coefficient for the different offset jets could be correlated by hX m / k a = c ( U j X m / ν ) 0.74 where X m is the distance to the maximum heat transfer location and the parameter c varies with the initial offset distance from 0.08 to 0.1. The profiles of the Nusselt number approach the results for a wall jet downstream of x / H j ≈ 8 and collapsed when scaled by Re j 0.77 in all cases.